2018
DOI: 10.3389/fpsyg.2018.00683
|View full text |Cite
|
Sign up to set email alerts
|

A Focused Review of Language Use Preceding Death by Execution

Abstract: Executions are one form of death that can be assumed to be maximally anxiety provoking. Words spoken by death row inmates moments before their execution can provide valuable insights into people's end-of-life communication needs and themes, conveying what individuals choose to express to others in the face of imminent death. In this focused review, we describe findings from quantitative and qualitative text analysis studies that have analyzed affective experiences and meaning-making attempts in transcriptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Further demonstrating that religion was a prominent feature of the final statements, the authors uncovered other important religious themes, such as preaching (15.8 percent), praying for others (13.4 percent), gratitude toward God (7.5 percent), prayer unspecified (6.8 percent), asking for God's forgiveness (6.8 percent), and prayer for self (6.5 percent). As alluded to above, studies documenting the most common themes found in the last statement data generally conclude that the themes are unexpectedly positive (Goranson et al 2017;Hirschmüller and Egloff 2018;Shermer 2018;Upton et al 2017) which is remarkable given the dire circumstances that death row inmates find themselves in at the moment of imminent death (Johnson et al 2014).…”
Section: The Last Statements Of Death Row Inmatesmentioning
confidence: 90%
See 1 more Smart Citation
“…Further demonstrating that religion was a prominent feature of the final statements, the authors uncovered other important religious themes, such as preaching (15.8 percent), praying for others (13.4 percent), gratitude toward God (7.5 percent), prayer unspecified (6.8 percent), asking for God's forgiveness (6.8 percent), and prayer for self (6.5 percent). As alluded to above, studies documenting the most common themes found in the last statement data generally conclude that the themes are unexpectedly positive (Goranson et al 2017;Hirschmüller and Egloff 2018;Shermer 2018;Upton et al 2017) which is remarkable given the dire circumstances that death row inmates find themselves in at the moment of imminent death (Johnson et al 2014).…”
Section: The Last Statements Of Death Row Inmatesmentioning
confidence: 90%
“…Since the mid-2000s, a small but burgeoning cottage industry of studies has documented the most common themes found in last statements (Heflick 2005;Egloff 2016, 2018;Schuck and Ward 2008;Shermer 2018;Vollum 2008;Vollum and Longmire 2009). A frequent observation is how surprisingly positive the themes are (Goranson et al 2017;Hirschmüller and Egloff 2018;Upton et al 2017). Last statements have also been used to assess the psychological make-up of death row inmates Kelly 2018, Foley andKelly 2018;Rice et al 2009), evaluate disparities in the content of last statements uttered by race and ethnic groups (Lester and Gunn 2013;McCaffree et al 2020), and explore religious coping strategies of inmates (Smith 2018(Smith , 2019.…”
Section: The Last Statements Of Death Row Inmatesmentioning
confidence: 99%
“… For a word cloud showing the words most commonly used by death row inmates executed in Texas between 1882 and 30 June 2015, see Hirschmüller and Egloff (2018). …”
mentioning
confidence: 99%